Incorporating 3D Laparoscopy for the Management of Locally Advanced Cervical Cancer: A Comparison with Open Surgery. Issue 4 (July 2016) - Raspagliesi, Francesco; Bogani, Giorgio; Martinelli, Fabio; Signorelli, Mauro; Chiappa, Valentina; Scaffa, Cono; Sabatucci, Ilaria; Adorni, Marco; Lorusso, Domenica; Ditto, Antonino
Purpose: To test the effects of the implementation of 3D laparoscopic technology for the execution of nerve-sparing radical hysterectomy. Methods: Thirty patients undergoing nerve-sparing radical hysterectomy via 3D laparoscopic (3D-LNSRH, n = 10) or open surgery (NSRH, n = 20) were studied prospectively. Results: No significant differences were observed in baseline patient characteristics. Operative times were similar between groups. We compared the first 10 patients undergoing 3D-LNSRH with the last 20 patients undergoing NSRH. Baseline characteristics were similar between groups (p>0.2). Patients undergoing 3D-LNSRH had longer operative time (264.4 ± 21.5 vs 217.2 ± 41.0 minutes; p = 0.005), lower blood loss (53.4 ± 26.1 vs 177.7 ± 96.0 mL; p<0.001), and shorter length of hospital stay (4.3 ± 1.2 vs 5.4 ± 0.7 days; p = 0.03) in comparison to patients undergoing open abdominal procedures. No intraoperative complication occurred. One (10%) patient had conversion to open surgery due to technical difficulties and the inability to insert the uterine manipulator. A trend towards higher complication (grade 2 or worse) rate was observed for patients undergoing NSRH in comparison to 3D-LNSRH (p = 0.06). Considering only severe complications (grade 3 or worse), no difference was observed (0/10 vs 2/20; p = 0.54). Conclusions: 3D-laparoscopic nerve-sparing radical hysterectomy is a safe and effective procedure. The implementation of 3D laparoscopic technology allows the execution of challenging operations via minimally invasive surgery, thus reducing open abdominal procedure rates. Further large prospective studies are warranted.